2019
DOI: 10.2106/jbjs.18.00372
|View full text |Cite
|
Sign up to set email alerts
|

Visit Duration Does Not Correlate with Perceived Physician Empathy

Abstract: Background: Perceived physician empathy is a strong driver of patient satisfaction. We assessed the influence of wait time, time spent with the surgeon, and surgeon stress level on the way patients rated surgeon empathy. Methods: One hundred and fourteen patients visiting 1 of 6 participating surgeons were prospectively enrolled in the study. We recorded patient demographics and assessed the patient rating of perceived physician empathy. Time waiting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
4
16
0
2
Order By: Relevance
“…Attending physicians trust the senior residents' performance/clinical judgement more than the junior (e.g., interns, PGY‐1) residents, for which the attending physicians may spend less time with the patients to avoid redundancies. Previous studies indicated that a provider “in‐hurry” phenomenon has an effect on patient perception of provider empathy; 17 these findings are quite controversial 23 and future studies are required to validate, or disprove, this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attending physicians trust the senior residents' performance/clinical judgement more than the junior (e.g., interns, PGY‐1) residents, for which the attending physicians may spend less time with the patients to avoid redundancies. Previous studies indicated that a provider “in‐hurry” phenomenon has an effect on patient perception of provider empathy; 17 these findings are quite controversial 23 and future studies are required to validate, or disprove, this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that a provider "in-hurry" phenomenon has an effect on patient perception of provider empathy; 17 these findings are quite controversial 23 and future studies are required to validate, or disprove, this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The time the physician spent in the room with the patient or if the caregiver believed the physician to be rushed during the visit did not affect perceived empathy. Kortlever et al similarly found that in the adult orthopedic population neither wait time nor time spent with the physician was independently associated with perceived physician empathy ( 19 ). It seems that caregivers can excuse shorter visits than desired and even the physician visibly rushing through the visit if sufficient empathy is demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study is the first Portuguese one to evaluate any differences in the patient perceived medical empathy with patients’ characteristics. On the other hand, some studies ( 21 , 22 ) found an association between patient perceived medical empathy and some physicians’ characteristics, namely exerting medical speciality and gender. Therefore, is patient’s perception of medical empathy more related to doctor-related factors than to patient-related ones?…”
Section: Discussionmentioning
confidence: 99%